(untitled) (World Bulletin of Social Sciences, 2021)
The article shows the concept of information technology, the role of using information technology in increasing the effectiveness of teaching natural sciences. Methods of teaching the subject of information technology are considered. The dominant activity in the field of social production is the collection, production, processing, storage, transmission and use of information. The modern means of microprocessor and computer technology, as well as based on various means of exchange of information, the active use of the intellectual potential of society and its members in scientific, industrial and other activities, the development of all spheres of social production, the intellectualization of labor activity, the combination of information technologies with scientific, industrial, information high-level services, access to reliable sources of information for any member of society, visualization of the information provided, the importance of the information used and constantly updated information technology, attention is paid to the effective use of an intermediary in the training of medical personnel